Assessing cilnidipine and its combination usage in Indian settings: a knowledge, attitude, and practice survey - Shete, Mukesh; Saxena, Ashish; Nakrani, Akshay; Shah, Chirag; Bhojwani, Heena; Jiwane, Dinesh (International Journal of Advances in Medicine, 2024)
Background: Hypertension, affecting 31% of the Indian population, is a major risk factor for cardiovascular diseases. Cilnidipine is used in its management, alone or in combination with ARB. The objective of the current KAP survey was to assess the knowledge of healthcare professionals (HCPs) regarding hypertension management, their attitudes toward its treatment, and the application of this knowledge in clinical practice. Method: A pan-India cross-sectional KAP survey was conducted from April 2022 to March 2023. The survey utilized a specially designed questionnaire focusing on various aspects of using cilnidipine and its combination with Telmisartan in hypertension management. A total of 1,254 HCPs with recognized qualifications participated. Descriptive statistics were employed for data analysis. Results: Around 56% of HCPs initiated monotherapy of an antihypertensive drug at an SBP level of 140 mmHg, while 57% initiated combination therapy at an SBP>160 mmHg. Nearly 43% reported initiating combination therapy in 20-30% of patients as initial treatment. Cilnidipine was preferred over amlodipine mainly due to decreased pedal edema. Cilnidipine monotherapy benefits young hypertensive patients (46%) and those with chronic kidney disease (CKD, 44%). Cilnidipine and telmisartan combination benefits patients with uncontrolled hypertension (46%), diabetes (43%), and CKD (41%). Advantages of this combination include less fluid retention, better compliance and tolerability, and less pedal edema. Conclusion: This KAP survey highlights current practices in hypertension management, emphasizing the use of cilnidipine and its combination, attributed to their favorable tolerability and suitability for diverse patient profiles.